Quality of life of students of a private medical college - Aziz, Yasir (Pak J Med Sci, 2020)
OBJECTIVE: To determine the quality of life of students of a private medical college in Karachi in Pakistan. METHODS: This cross sectional study was conducted among 217 medical students of Liaquat College of Medicine and Dentistry, Karachi from June 2017 to March 2018. Students were selected by a stratified sampling method and the World Health Organization Quality of Life BREF Instruments (WHO QOL-BREF) was used for the above-mentioned study. Statistical analysis was performed using SPSS (Statistical Package for Social Sciences) version 21 and Analysis of variance (ANOVA). Independent t-test was used as p <0.05 significant. RESULTS: A total of 250 questionnaires were distributed among 2(nd) year, 3(rd) year, 4(th) year and final year students and the response rate was 86.8%. Among them 48.5% (n=105) students were male and 51.5% (n=112) students were female, while 9.2% (n=20) students were currently ill and the other 90.8% (n=197) were healthy. CONCLUSION: Medical education influences the quality of life (QOL) of students adversely. Social relationships and environmental domain were satisfactory in private medical institutes whereas physical and psychological progress was low due to academic load which requires improvement either by physical activities such as fitness classes or other extra-curricular activities.